Converging the Evolution of Router Architectures and IP Networks. - Csaszar, A. (IEEE Network : the magazine of global information exchange)
Although IP is widely recognized as the platform for next-generation converged networks, unfortunately, it is heavily burdened by its heritage of almost 30 years. Nowadays, network operators must devote significant resources to perform essential tasks, such as traffic engineering, policy enforcement, and security. In this article, we argue that one of the principal reasons for this is the way control and forwarding planes are interspersed in IP networks today. We review the architectural developments that led to the current situation, and we reason that centralization of network control functionality can constitute a solution to the pressing problems of the contemporary Internet.